Self-Reported Sleep and Exercise Patterns in Patients with Schizophrenia: a Cross-Sectional Comparative Study - Nancy Kiwan (12451992) (2019)
Background Adequate sleep and physical activity have been linked to the overall well-being of both medical and psychiatric patients. Patients with schizophrenia have shown abnormal sleep patterns and decreased physical activity that were linked to their psychopathology and physical health. These phenomena are not studied yet in Arab patients with schizophrenia. The purpose of this study is to study the sleep and exercise patterns in Arab patients with schizophrenia compared with those of healthy controls. Method A total of 99 patients with schizophrenia and 101 controls were recruited. Arabic versions of sleep, exercise, socio-demographic, and clinical questionnaires were administered as well as the validated scales to measure psychopathology, depression, and suicidality in these participants. Results The majority of patients with schizophrenia slept more than 8 h per day and exercised less when compared with controls. Sleep quality was worse in those with higher depression score and higher suicidality scores were seen in patients with lower sleep duration. Multinomial regression showed that patients with schizophrenia have higher odds of sleeping more than 8 h even after controlling for the intake of antipsychotics, age, gender, smoking status, and other confounding factors. Conclusion Our results showed that Arab patients with schizophrenia are at increased risk of having longer sleep duration with inadequate physical activity, which are correlating with worsening of depressive symptoms and suicidality. Thus, more attention should be paid to the changes in sleep patterns and level of exercise when treating Arab patients with schizophrenia. Correction: Self-Reported Sleep and Exercise Patterns in Patients with Schizophrenia: A Cross-Sectional Comparative Study: https://doi.org/10.1007/s12529-020-09851-2, published online 22 January 2020.